Perbandingan Sistem Pemerintahan Presidensial dalam Sistem Ketatanegaraan di Indonesia dan Iran - Sultoni Fikri; Anang Fajrul Ukhwaluddin (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2022)
Abstract--This paper describes a comparison related to the presidential government system in the Unitary State of the Republic of Indonesia and the State of the Islamic Republic of Iran. Some of the basic reasons that make the writer interested in discussing presidential government systems are the existence of standard rules or at least oriented to the United States presidential government system, but in practice, the system tends to follow the conditions of the socio-political-cultural structure that exists in each country. While the background why the author chose Indonesia and Iran to be compared, at least based on several factors. First, related to the history of upheaval in each country, Indonesia has experienced a period of reform and Iran has experienced a period of revolution. Second, Indonesia and Iran are both countries with a majority Muslim population, and Iran makes Islamic values ??the basis of state life. Meanwhile, in Indonesia, Islamic values ??are not fully used as the basis of the state, considering that Indonesia is a diverse country in terms of religion and culture. Third, Indonesia and Iran both use a presidential system of government, but Indonesia and Iran can combine the rules of a presidential government system with the conditions of the socio-political-cultural structure that exist in each country. This research is research using the statutory approach, conceptual approach, and comparative approach. As a result, there are differences in the implementation of presidential government systems in Indonesia and Iran in several indicators. This is very reasonable because the system of government in a country must adapt to the socio-political historical conditions that exist in both Indonesia and Iran. Indonesia, Iran, presidential system.